G Protein–Coupled Receptor Oligomerization Revisited: Functional and Pharmacological Perspectives - Ferré, Sergi; Casadó, Vicent; Devi, Lakshmi A.; Filizola, Marta; Jockers, Ralf; Lohse, Martin J.; Milligan, Graeme; Pin, Jean-Philippe; Guitart, Xavier (Pharmacological reviews, 2014)
Most evidence indicates that, as for family C G protein–coupled receptors (GPCRs), family A GPCRs form homo- and heteromers. Homodimers seem to be a predominant species, with potential dynamic formation of higher-order oligomers, particularly tetramers. Although monomeric GPCRs can activate G proteins, the pentameric structure constituted by one GPCR homodimer and one heterotrimeric G protein may provide a main functional unit, and oligomeric entities can be viewed as multiples of dimers. It still needs to be resolved if GPCR heteromers are preferentially heterodimers or if they are mostly constituted by heteromers of homodimers. Allosteric mechanisms determine a multiplicity of possible unique pharmacological properties of GPCR homomers and heteromers. Some general mechanisms seem to apply, particularly at the level of ligand-binding properties. In the frame of the dimer-cooperativity model, the two-state dimer model provides the most practical method to analyze ligand–GPCR interactions when considering receptor homomers. In addition to ligand-binding properties, unique properties for each GPCR oligomer emerge in relation to different intrinsic efficacy of ligands for different signaling pathways (functional selectivity). This gives a rationale for the use of GPCR oligomers, and particularly heteromers, as novel targets for drug development. Herein, we review the functional and pharmacological properties of GPCR oligomers and provide some guidelines for the application of discrete direct screening and high-throughput screening approaches to the discovery of receptor-heteromer selective compounds.